Host response genes associated with nodular gastritis in Helicobacter pylori infection. Issue 5 (8th May 2018) - Ikuse, Tamaki; Ohtsuka, Yoshikazu; Obayashi, Naho; Jimbo, Keisuke; Aoyagi, Yo; Kudo, Takahiro; Asaoka, Daisuke; Hojo, Mariko; Nagahara, Akihito; Watanabe, Sumio; Blanchard, Thomas G; Czinn, Steven J; et al.
Abstract: Background: Chronic Helicobacter pylori infection in children induces lymphoid hyperplasia called nodular gastritis (NG) at the antral gastric mucosa. The aim of this study was to evaluate genes in gastric biopsy on microarray analysis, to identify molecules associated with NG on comparison with NG‐negative pediatric corpus tissue and with H. pylori ‐infected adult tissue with atrophic gastritis (AG). Methods: Eight pediatric and six adult H. pylori ‐infected patients, as well as six pediatric and six adult uninfected patients were evaluated. All infected adults had AG. NG was observed in the antrum of all eight pediatric patients and in the corpus of three patients. Adult and uninfected patients were free of NG; that is, only pediatric H . pylori ‐infected patients had NG. Total RNA was purified from gastric biopsy, and microarray analysis was performed to compare gene expression between groups. The three infected children with NG in both the antrum and corpus were excluded from analysis of corpus samples. Results: The number of genes significantly up‐ or downregulated (fold change >3, P < 0.01) compared with uninfected controls varied widely: 72 in pediatric antrum, 45 in pediatric corpus, 103 in adult antrum and 71 in adult corpus. Nineteen genes had significantly altered expression in the antrum of NG tissue compared with NG‐negative pediatric corpus tissue and adult AG tissue. The CD20 B‐cell specific differentiation antigen had the most pronounced increase. Previously described regulators of NG development were not predominantly upregulated in the NG mucosa. Conclusions: CD20 overexpression may play an important role in lymphoid follicle enlargement and NG.